Cyber-enhanced canine suit with wide-view angle for three-dimensional LiDAR SLAM for indoor environments. (2nd June 2020) - Beokhaimook, Chayapol; Ohno, Kazunori; Westfechtel, Thomas; Nishinoma, Hiroyuki; Tamura, Ryoichiro; Tadokoro, Satoshi
Abstract : Understanding the topographical information of the disaster site can enhance the efficiency and safety of search and rescue missions. This study describes the development of a cyber-enhanced canine suit for three-dimensional (3D) simultaneous localization and mapping within indoor environments. The suit's weight was approximately 3.0 kg and was compatible with large dogs ( > 30.0 kg). It could collect dense, wide view-angle, and long-range 3D point clouds. The collected point clouds were processed offline to create 3D maps. The suit was equipped with a protective cover that could prevent physical damage to the light imaging detection and ranging (LiDAR) sensor from collision. The protective cover was designed to (a) eliminate any effects on the performance of the 3D LiDAR and (b) sustain the stress from the impact at the velocity of 20.0 m/s with no physical damage. Additionally, the canine suit was also modified for better fitting and stability of the LiDAR on a wider range of dog bodies. The performance of the suit was demonstrated on real dogs in four different scenarios in areas with different space sizes, dog gait patterns, and ground layouts. The space size and position errors observed did not exceed 0.80% and 1.13%, respectively. GRAPHICAL ABSTRACT: UF0001